2016
DOI: 10.1055/s-0041-109592
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillektomie bei PANDAS?

Abstract: establishing the diagnosis of PANDAS is complicated by underlying co-morbidities in the field of neurology-psychiatry and the lack of a reliable biomarker. The positive outcome after TE as reported in case studies may be influenced by the postoperative medication and is not supported by the results of large-scale studies. In the light of the considerable postoperative morbidity and unavoidable mortality rate it appears wise to indicate TE only in clinical studies with standardized inclusion criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…Limitations of PANDAS treatment research also include a lack of consensus regarding treatment remedies and their hypothesized neurological action. A German case study review found that tonsillectomies had positive outcomes for children with PANDAS, but this may have been a result of post-operative treatment with antibiotics (Windfuhr, 2016). Considering the proposed travel of GAS-specific T cells through NALT after multiple exposures to the bacteria, the efficacy of tonsillectomies should be studied during various intervals, including initial symptoms or repeated infections.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of PANDAS treatment research also include a lack of consensus regarding treatment remedies and their hypothesized neurological action. A German case study review found that tonsillectomies had positive outcomes for children with PANDAS, but this may have been a result of post-operative treatment with antibiotics (Windfuhr, 2016). Considering the proposed travel of GAS-specific T cells through NALT after multiple exposures to the bacteria, the efficacy of tonsillectomies should be studied during various intervals, including initial symptoms or repeated infections.…”
Section: Discussionmentioning
confidence: 99%
“…(povlačenje simptoma oko 50 %) i plazmafereza (9,10). Najnovija istraživanja pokazala su da tonzilektomija može imati povoljan efekat (11).…”
Section: Klinička Slikaunclassified
“…Ukoliko antibiotska terapija ne rezultira poboljšanjem, primjenjuju se imunoglobulini, kortikosteroidi, plazmafereza. Nova istraživanja su pokazala da tonzilektomija može imati povoljan učinak na smanjenje simptoma bolesti (11).…”
Section: Diskusijaunclassified